Adaptive Behavior of Farmers after Water Right Reform from the Perspective of Prospect Theory - WAN Fubing; SUN Boming; DAI Xiaoping (Renmin Zhujiang)
In an uncertain environment,the adaptive behavior of farmers after the reform of the water right system affects the reform effect of water rights.Most existing studies have regarded farmers as entirely rational actors,and there is still a lack of theoretical analysis and quantitative description of farmers' behavior based on the assumption of bounded rational behavior.Therefore,prospect theory is introduced to study the adaptive behavior of farmers under the conditions of total water right control and water right trading.Taking two irrigation districts in the Shiyang River Basin into account,this paper analyzes the planting structure adjustment,irrigation area selection,and water right trading behavior of farmers under the conditions of reducing the total irrigation water by 5%,15%,and 25%.It is found that in the condition of water right reduction,the optimal decision for growing wheat and maize is ‘adjustment and water purchase’,and the worst decision is ‘reducing irrigation area’.The effect of water right reduction on the prospect value of maize is greater than that of wheat.The prospect value of different decisions varies monotonically with the proportion of reduction in water use.The results show that the prospect theory model can better describe the adaptive behavior of farmers and can provide a reference for the simulation and regulation of agricultural water right reform.